KOPING STRES WANITA MENIKAH YANG BELUM DIKARUNIAI ANAK - GANTINA KOMALASARI; RIZKA SEPTIYANTI (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Getting married is a phase in the cycle of human life. The purpose of marriage are very diverse one of which is the desire to have a child as a complement in a family. For some people in Indonesia, to have children as the successor of their generations is a must. Even though most of married couple want to have a child, but unfortunately not every married couple are blessed with child. This can be caused by several factors, one of which is a biological factor, namely infertility. This study was conducted to determine coping strategies that are more often used by married women while facing the stress due to not having children. This study used quantitative method. The instrument used to measure coping stress is a modified inventory of The Ways of Coping (WOC) and associated with a stressor of infertility from The Infertility Problem Inventory (FPI) with coefficient Cronbach Alpha 0,88. The sample for this study is 42 subjects, with non-probability sampling technique and incidental technique. Data was analyzed using Winstep software (RASCH Model) version 3.73 and SPSS version 16.0. The result of this research shows that married women more often use emotion focused coping strategy in facing stress because haven’t been blessed with child, with percentage equal to 67,33%.